Slow light through Brillouin scattering in continuum quantum optomechanics - Zoubi, Hashem; Hammerer, Klemens (Frontiers in Quantum Science and Technology, 2024)
We investigate the possibility of achieving a slow signal field at the level of single photons inside nanofibers by exploiting stimulated Brillouin scattering, which involves a strong pump field and the vibrational modes of the waveguide. The slow signal is significantly amplified for a pump field with a frequency higher than that of the signal, and attenuated for a lower pump frequency. We introduce a configuration for obtaining a propagating slow signal without gain or loss and with a relatively wide bandwidth. This process involves two strong pump fields with frequencies both higher and lower than that of the signal, where the effects of signal amplification and attenuation compensate each other. We account for thermal fluctuations due to the scattering off thermal phonons and identify conditions under which thermal contributions to the signal field are negligible. The slowing of light through Brillouin optomechanics may serve as a vital tool for optical quantum information processing and quantum communications within nanophotonic structures.